The Effect of Firm Characteristics on Tax Avoidance with Liquidity as a Moderating Variable in Indonesian Firms - Hidayatul Akma; Putra, I Nyoman Nugraha Ardana; Pituringsih, Endar (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to analyze the effect of capital intensity, profitability, and leverage on tax avoidance, as well as to examine the role of liquidity as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange during 2020–2024. Methodology/approach: The research employed a quantitative associative approach using panel data regression with the Moderated Regression Analysis (MRA) technique. The sample consists of 151 companies (755 firm-year observations) selected through purposive sampling. Data were analyzed using the Fixed Effect Model based on Chow, Hausman, and LM tests. Findings: The results showed that profitability had a significant positive effect on tax avoidance, while capital intensity and leverage did not. Liquidity proved to be a pure moderator, weakening the effect of capital intensity and leverage on tax avoidance, but it was unable to moderate the effect of profitability. Practical implications: The findings highlight the importance for regulators to consider firms’ liquidity conditions when designing tax enforcement policies, as financially strong firms tend to show higher voluntary compliance. Originality/value: This study contributes by incorporating liquidity as a moderating variable in the relationship between internal firm characteristics and tax avoidance an approach rarely examined in prior Indonesian tax compliance research